集中治療室で終末期を迎える患者の治療選択における家族の解放的意思決定を支える看護実践 - 尾之上 智世; 北村 愛子 (日本看護倫理学会誌, 2025)
集中治療室で終末期を迎える患者の治療選択における家族の解放的意思決定を支える看護実践を明らかにするために「集中治療に携わる看護師のクリニカルラダー」レベルⅥ以上の看護師11人に対し半構造化面接を行った。10カテゴリーが生成され、《家族の様子から理解の程度を推し量る》、《治療選択に関わる人々の関係性を把握する》、《話すことへの制約がかかっている状況を把握する》、《理解を深めるために現状を分かりやすく説明する》、《家族が理解できるように医師にはたらきかける》、《率直に話せる環境を整える》、《家族の悩みを共に考える》、《他の家族と助け合い決定できるように導く》、《家族の苦悩を受け止め力づける》、《納得した上で決定することができたか家族の言動から評価する》が明らかになった。今回、明らかになった支援内容を積極的に実践やカンファレンスで活用し医療チームで解放的意思決定を支えていく必要があると考える 　The present study aimed to clarify the nursing practice to assist family members’emancipated decisionmaking（EDM）in choosing treatment options for patients facing terminal stages in the intensive care unit. Eleven nurses with Level Ⅵ and higher certifications from the “Clinical Ladder for Nurses Attending Intensive Care Practice”underwent a series of semi-structured interviews. Subsequently, ten categories were generated, including 〈Assessing family members’understanding regarding patient’s condition from their appearances〉,〈Grasping the relationships among those involved in choosing treatment options〉,〈Understanding circumstances where family members hesitate to discuss treatment options〉,〈Explaining patient’s current conditions clearly to deepen the family members’ understanding〉,〈 Coordinating family meeting with doctors to help family members to understand the patient’s conditions〉,〈 Providing family members with a space and opportunity for honest discussion〉,〈 Attending to family members’concerns〉,〈 Assisting all family members to help each other to reach the treatment decision〉,〈Accepting family members’ sufferings and encourage them〉, and 〈Assessing from family members’speech and behavior if they reached decisions with confidence〉. As this study demonstrated, medical teams must actively use the above-mentioned support contents in case conferences and nursing practice to aid patients’and their families’EDM.